The visual books lost to the visual narrators through the book of the history of Damascus to Ibn Assaker - Banan Fakhir Yusuf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Ibn Asakir is a great historian who has a historical legacy, thanks to the eighty volumes, who were authored by the richest Islamic libraries with this huge book. In the history of Damascus, but most of those books were lost and deprived of the minds of researchers Ibn Asakir borrowed many novels and texts from visual books. Most of these books are lost books, of which only the name of the book and its historian remain, which indicates the scientific prosperity and sophistication that prevailed at that time. The loss of those books, because Basra its scholars and their arrival were not in the few category, rather it was a school and a place for science and scholars, and these books became texts and novels scattered in the stomachs of other books.,